ANALISIS KOMPARASI TINGKAT RISIKO PEMBIAYAAN JUAL BELI DENGAN BAGI HASIL PADA BANK MUAMALAT KCP. BONE - Ahmad Rafi (Islamic Banking and Finance, 2021)
Despite a fairly rapid development of Islamic Banking in Indonesia, but the composition of cost is still imbalance. This is proved by the nomination of skim murabahah (consumptive sale and purchase) compared with skim mudarabah (products division/productive). The cost of mudarabah is the cost of real sector and considered has high risk. Therefore, syariah bank needs to apply risk management and evaluate the level of maximum risk that might happen on the costs spent. The data were analyzed using credit risk method. Credit risk is a model of risk measurement of costs portfolio. This model was introduced by Credit Suisse Financial Products (CSFP) in 1997.This approach wasmaximum loss measurement from default credit portfolio. Data input credit risk are as follow; (exposure of default, default rates, probability of default, and expected loss) after having results of data analysis and then were analyzed using trend analysis to measure the frequency of risk level happened in the period of 2013-2014 and used analysis of hypothesis test one sample T test to obtain the comparison of risk level of sale and purchase of product division. The results of trend analysis express that the frequency of the occurrence of financial risks is more dominant on the sale and purchase contract, it can be seen in June 2013 until December 2014 NPF murabahah continuously improved, it is different with mudarabah (product division) that still run well. While the results of comparative test analysis One sample T test state that the cost of murabahah contract has higher risk measured from the high costs of financing bogged down experienced in this case the collectability category 5 at the end has impact on the level of achievement of profitability of Muamalat banks.